2007
DOI: 10.1055/s-2007-976551
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes for Pregnant Women with Vaginal-Rectal Carriage of Community-Associated Methicillin-Resistant Staphylococcus aureus

Abstract: The purpose of this study was to determine the predictors and outcomes of pregnant women with vaginal-rectal carriage of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA). We performed an unmatched 1:4 case-control study with two control groups (13 CA-MRSA cases, 52 methicillin-sensitive S. aureus (MSSA) controls, and 52 S. aureus-negative controls) via a retrospective medical record review. We found that CA-MRSA cases were 12.5 times significantly less likely to be colonized with grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…Conversely, MSSA colonization was more frequent in GBS-positive women (8). Of note, the rates of GBS colonization in the control groups were 46 to 50% (8,33), which is higher than the generally reported rates of 10 to 30% (29). In contrast, others have reported that both MSSA and MRSA colonization were significantly more common in GBS-positive women (2).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Conversely, MSSA colonization was more frequent in GBS-positive women (8). Of note, the rates of GBS colonization in the control groups were 46 to 50% (8,33), which is higher than the generally reported rates of 10 to 30% (29). In contrast, others have reported that both MSSA and MRSA colonization were significantly more common in GBS-positive women (2).…”
Section: Discussionmentioning
confidence: 68%
“…Two reports demonstrated a decreased frequency of MRSA colonization in the on May 9, 2018 by guest http://jcm.asm.org/ setting of GBS colonization (8,33). Conversely, MSSA colonization was more frequent in GBS-positive women (8). Of note, the rates of GBS colonization in the control groups were 46 to 50% (8,33), which is higher than the generally reported rates of 10 to 30% (29).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A significant association between S. aureus colonization and Group B streptococcus (GBS) colonization was found. In a subsequent study this association was analyzed in more detail [66] and the significant association between MSSA and GBS was confirmed. Pregnant women with MSSA carriage were significantly more likely to have postpartum fever than those who were S. aureus-negative.…”
Section: Eradication Of Intestinal Carriagementioning
confidence: 90%